Absolute adsorption of light hydrocarbons on organic-rich shale: An efficient determination method. (15th January 2022) - Huang, Xing; Gu, Lijun; Li, Shuaishuai; Du, Yifan; Liu, Yueliang
Graphical abstract: Highlights: Excess adsorption underestimates actual adsorption of shale gas in reservoirs. Absolute adsorption is higher than excess adsorption, especially at higher pressures. SLD theory is a more efficient method in determining absolute adsorption. Abstract: Absolute adsorption has been found being more accurate than directly measured excess adsorption value for estimating the in-situ shale gas-in-place storage. To obtain accurate absolute adsorption, traditional methods determined the adsorbed gas density using complicated molecular simulation methods, which is employed to correct the measured excess value. In this work, excess adsorption, which is deemed to be inaccurate in previous work, of CH4 and C3 H8 is first measured on three typical shale rocks. The adsorbed-layer density is then reasonably calculated using the simplified local density theory (SLD) to obtain corresponding absolute adsorption of CH4 and C3 H8 . It is found that the adsorbed layer density calculated from SLD theory is comparable to that obtained from molecular simulation methods, while it is more efficient for the density computation. Compared to CH4, C3 H8 presents stronger adsorption capacity on shale rocks, suggesting that C3 H8 is more affinity to organic shale. The CH4 ′s absolute adsorption is stronger than its excess value and their deviation enlarges as pressure increases, while absolute adsorption for C3 H8 is found to be more or less the same with the measured excess value. The importance of this work lies in that we propose a new method for efficiently obtaining the adsorbed-layer density, which is crucial for accurately determining gas and oil storage in shale reservoirs.